Pistas orgânicas: uma atividade lúdica para o ensino das funções orgânicas - Silva, Janduir Egito da (2013)
Educational games can work as a complementary tool in teaching and learning chemistry, playing an important role in the development of the students cognitive structures, familiarizing them with certain conceptual content, which may arouse interest in the study of such content. In this work, we made an analysis of organic chemistry textbooks recommended by Programa Nacional do Livro Didático 2012, for high school students in order to verify the existence of methodological proposals using educational games. From this analysis, we proposed an educational game to be developed for students on 3º year of high medium and undergraduate chemistry, that are in 1º semester of the course, which is constituted of a tray and 48 letters, which work various concepts concerning organic functions, such as: structural characteristics, physical properties, chemical and properties diverse of the compounds used for the confection of the letters. The game was applied to a class degree in chemistry, period 2012.1 to a Federal Education of Rio Grande do Norte and a group of students of the 3rd year of the state schools of Rio Grande do Norte, in the period the months of April and May 2012. The analysis of the performance of the game proposed was made using visual observations, photographic records and testimonials of students who participated in the games. The instrument used for the data collection was the student questionnaire, which was similar for both groups, differing only in the amount of questions, because one of them had one more question. During application of the game it was observed that it constitutes a dynamic strategy in the teaching and learning of chemistry concepts, given that students actively participated in the classes as well, demonstrated more motivation in the construction of concepts, furthermore, it was possible to observe evidence of other possibilities of the game. This could be verified through visual observations and testimonials at the end of each game, by reading the answers to the questionnaires